"It's the people that keep me here": Exploring the role of community attachment in increasing length of residency. (August 2019) - Kanakis, K.; McShane, C.J.; Kilcullen, M.L.; Swinbourne, A.L.
Abstract: The increasing transient population within rural and remote communities challenges the sustainability of regional Australia. Challenges to sustainability are particularly present for mining communities that have an increasing reliance on transient workforces. Identifying ways to increase length of residency within mining communities could assist in increasing the economic and social stability of these communities. The aim of this qualitative research was to explore residents' intentions to stay and factors that increased their intentions to leave a remote mining community. Twenty residents (three males, 17 females) recruited from a remote mining community in Queensland, Australia, participated in interviews. Interview data was analysed using thematic analysis within an interpretative phenomenological analysis framework. The participants reported their connection to people and place was their predominant motivation for wanting to stay in the community. The main reasons that participants reported wanting to leave the community was a perceived lack of access to family, services and employment, and lifestyle factors. Additionally, some participants reported intentions to leave as they perceived that the community was not their permanent home. These findings provide practical insight into strategies that could be developed to increase length of residency. For example, improving community attachment and satisfaction through promoting awareness of the available services and activities in which residents can participate. Through these strategies for increasing the length of residency within regional communities, the sustainability of these communities may then in turn be enhanced. Highlights: Intentions to stay and factors that increase intentions to leave were explored. Connection to people and place was a predominant motivation for wanting to stay. Improving community attachment and satisfaction may improve intentions to stay.